Impaired adaptive response to mechanical overloading in dystrophic skeletal muscle. - Pierre Joanne; Christophe Hourdé; Julien Ochala; Yvain Caudéran; Fadia Medja; Alban Vignaud; Etienne Mouisel; Wahiba Hadj-Said; Ludovic Arandel; Luis Garcia; Aurélie Goyenvalle; Rémi Mounier; et al. (PLoS ONE)
Dystrophin contributes to force transmission and has a protein-scaffolding role for a variety of signaling complexes in skeletal muscle. In the present study, we tested the hypothesis that the muscle adaptive response following mechanical overloading (ML) would be decreased in MDX dystrophic muscle lacking dystrophin. We found that the gains in muscle maximal force production and fatigue resistance in response to ML were both reduced in MDX mice as compared to healthy mice. MDX muscle also exhibited decreased cellular and molecular muscle remodeling (hypertrophy and promotion of slower/oxidative fiber type) in response to ML, and altered intracellular signalings involved in muscle growth and maintenance (mTOR, myostatin, follistatin, AMPKα1, REDD1, atrogin-1, Bnip3). Moreover, dystrophin rescue via exon skipping restored the adaptive response to ML. Therefore our results demonstrate that the adaptive response in response to ML is impaired in dystrophic MDX muscle, most likely because of the dystrophin crucial role.